Fibro-indices versus liver stiffness for prediction of significant fibrosis in hepatitis B virus-infected Egyptian patients; a single-center experience. (3rd March 2020) - Said, Mohamed; Eletreby, Rasha; Omar, Heba; Dabees, Hossam; Abdelghafour, Reem; El-Serafy, Magdy; Doss, Wahid
ABSTRACT: Background : Liver fibrosis assessment is a key factor for disease management in hepatitis B virus (HBV). Several serum biomarkers have been introduced for noninvasive fibrosis assessment. This study aims to evaluate the validity of simple noninvasive indices, namely Fibrosis-4 score (FIB4), aspartate aminotransferase (AST) to Platelet Ratio Index (APRI), Goteborg University Cirrhosis Index (GUCI), and fibrosis index in evaluation of liver fibrosis in chronic HBV. Methods : 226 patients with chronic HBV genotype D were included. FIB4, APRI, GUCI, and fibrosis index were performed. Receiver operating characteristic (ROC) curves were used to predict ≥F2 fibrosis. Results : The mean age of patients was 39.00 years and 72.27% of patients were treatment naïve. Patients with ≥F2 hepatic fibrosis had significantly higher FIB-4 (1.58 ± 1.46 vs. 1.15 ± 1.09), APRI (0.68 ± 0.71 vs. 0.43 ± 0.37), GUCI score (0.75 ± 0.94 vs. 0.42 ± 0.29) and Fibrosis index (2.18 ± 0.84 vs. 1.84 ± 0.69). All studied indices were able to diagnose ≥F2 fibrosis. APRI had the highest area under the ROC (AUROC) of 0.67. Predictivity of all indices was higher in on-treatment vs naive patients. Conclusion : FIB4, APRI, and GUCI scores are acceptable, noninvasive, and cheap simple indices that can be helpful on treatment follow-up of fibrosis regression in the setting of low socioeconomic conditions compared to the relatively expensive fibroscan modality.